REVENUE SHARING CONTRACT AS COORDINATION MECHANISM WITH THE IMPLEMENTATION OF LOGISTICS OUTSOURCING IN DECENTRALIZED SUPPLY CHAIN - Winda Narulidea; Artya Lathifah (Journal of Engineering and Management in Industrial System, 2017)
By making logistics outsourcing decision, companies have been able to improve the logistics performance, maintain focus on core business, and minimize distribution cost. However in decentralized condition, there is only limited control of the third party logistics service provider (TPLSP), whose logistics service performance affect the products availability, quality, price, and market share. In this research, a model is developed as coordination mechanisms with the implementation of logistics outsourcing in decentralized supply chain. Revenue sharing contract model is developed in the proposed model to coordinate the supply chain consisting of manufacturers, TPLSPs, and retailers. Moreover the incentive and penalty scheme are implemented in accordance to the supply chain logistics service performance, so the risks and the necessary costs could be allocated to all players. To increase the desirability level of the contracts for all players, the contracts parameters are determined so that all players could obtain higher profit than in a common decentralized supply chain conditions, furthermore the win-win condition can be achieved. This paper provides new model of coordination mechanism in supply chain with logistics outsourcing and offers the incentive and penalty scheme into the basic model of revenue sharing contracts.